Where Culturally Responsive Pedagogy Meets Fieldwork: Engaging Luganda Learners Through Socio-Cultural Expressions - David Kabugo (Journal of Language, Literature, and Educational Research, 2026)
Purpose of the study: This study examined whether simple fieldwork data-collection tools could improve Senior Six students’ engagement when learning socio-cultural expressions in Luganda. Methodology: A five-week pilot cluster experiment was conducted in three rural Ugandan advanced-level schools. Six intact Luganda classes were assigned by stream to a fieldwork-tool condition or a comparison condition. Data came from an engagement scale, classroom observations, project scores, journals, teacher logs, and student interviews. Main Findings: Students who used interview guides, proverb logs, observation forms, reflective journals, and presentation planners showed stronger engagement than students taught mainly through teacher explanation, board notes, and textbook discussion. The largest gains were seen in participation, task completion, project talk, and the ability to connect classroom texts with community meanings. Novelty/Originality of this study: The study shows how low-cost, relationship-centred fieldwork routines can turn Luganda socio-cultural content from memorised knowledge into inquiry. It contributes a practical model for using community knowledge ethically in local-language classrooms without relying on expensive technology.